Answer:
Step-by-step explanation:
9x2 + 6x. = 3x(3x + 2). Answer: 3x(3x + 2). 2. Simplify: (-7x2 - 3x) - (4x2 - x) Solution: ... -2(2x + 5)<u> </u><u><em>Answer: -2(2x + 5) 8. Simplify:(8+4x)/4x. </em></u>Solution: (8+4x)/4x = 4(2 + x)/4x ... Compare the above equation 3x2 – 5x + 1 =0 with ax2 + bx + c = 0
hope this helps. : )
please leave feedback if you have any questions thx
Answer:
2x + 4y = 4
-8x + 8y = -16.
Step-by-step explanation:
We can find an equivalent system by multiply the 2 equations by 2.
x + 2y = 2 multiplied by 2 is 2x + 4y = 4.
Eighty three thousand four hundred and seventy nine
Answer:
i think it would be a model.
Step-by-step explanation: